2002
DOI: 10.1152/ajpgi.00315.2001
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin activity is not involved in premature, intrapancreatic trypsinogen activation

Abstract: Halangk, Walter, Burkhard Krü ger, Manuel Ruthenbü rger, Jö rg Stü rzebecher, Elke Albrecht, Hans Lippert, and Markus M. Lerch. Trypsin activity is not involved in premature, intrapancreatic trypsinogen activation. Am J Physiol Gastrointest Liver Physiol 282: G367-G374, 2002. First published September 21, 2001 10.1152/ajpgi.00315.2001.-A premature and intracellular activation of digestive zymogens is thought to be responsible for the onset of pancreatitis. Because trypsin has a critical role in initiating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 30 publications
2
74
0
2
Order By: Relevance
“…Destruction of this "failsafe mechanism" by the R122H mutation would increase intrapancreatic trypsin activity and eventually precipitate pancreatitis. Halangk et al demonstrated that autodegradation of trypsin mitigates cathepsin B-mediated trypsinogen activation during cerulein-induced zymogen activation in isolated rat acini, suggesting that an autolytic failsafe mechanism might be operational in the mammalian pancreas [21]. Biochemical evidence supports the notion that Arg122 is important for autolysis of trypsin [15,16,[22][23][24][25][26] and mutations of this amino-acid result in increased trypsin stability [16,23,26].…”
Section: Model #1 Increased Trypsin Stability Causes Hereditary Pancmentioning
confidence: 97%
See 1 more Smart Citation
“…Destruction of this "failsafe mechanism" by the R122H mutation would increase intrapancreatic trypsin activity and eventually precipitate pancreatitis. Halangk et al demonstrated that autodegradation of trypsin mitigates cathepsin B-mediated trypsinogen activation during cerulein-induced zymogen activation in isolated rat acini, suggesting that an autolytic failsafe mechanism might be operational in the mammalian pancreas [21]. Biochemical evidence supports the notion that Arg122 is important for autolysis of trypsin [15,16,[22][23][24][25][26] and mutations of this amino-acid result in increased trypsin stability [16,23,26].…”
Section: Model #1 Increased Trypsin Stability Causes Hereditary Pancmentioning
confidence: 97%
“…The complex properties of the R122C mutant were first interpreted as an example of a loss-offunction PRSS1 mutation associated with hereditary pancreatitis, suggesting that a trypsinogen mutation could cause pancreatitis by eliminating a trypsin-dependent protective mechanism [36]. Additional support for this hypothesis came from earlier studies indicating that trypsin autodegradation might play a protective role in cerulein-induced zymogen activation [21]. Although this model is provocative, the bulk of results from in vitro experiments using recombinantly expressed trypsinogen mutants remains inconsistent with it, as a loss of function could not be demonstrated for the large majority of mutations (Table 2).…”
Section: Model #4 Loss Of Trypsin Function In Hereditary Pancreatitimentioning
confidence: 99%
“…6 and references therein). Inactivation of intrapancreatic trypsin through trypsin-mediated trypsin degradation (autolysis) or by an unidentified serine protease (enzyme Y) was therefore proposed to be protective against pancreatitis (7)(8)(9)(10)(11). This notion received support from the discovery that the R122H mutation, which eliminates the Arg 122 autolytic site in cationic trypsinogen, causes autosomal dominant hereditary pancreatitis in humans (9).…”
mentioning
confidence: 99%
“…In inhibitor wash-out experiments, it was determined that, following hormone-induced trypsinogen activation in pancreatic acinar cells, 80% of the active trypsin is inactivated immediately and directly by trypsin itself. Taken together, these experiments suggest that trypsin activity is neither required nor involved in trypsinogen activation, that trypsinogen does not autoactivate in living pancreatic acinar cells, and that its most prominent role is in autodegradation [55]. This, in turn, suggests that intracellular trypsin activity might have a role in the defense against other, potentially more harmful digestive proteases.…”
Section: Role Of Trypsin In Premature Digestive Protease Activationmentioning
confidence: 86%
“…Therefore, isolated pancreatic acini and lobules offer an alternative to study the role of trypsin in pancreatitis. In a recent study that used a specific, cell permeant and reversible trypsin inhibitor, it was found that complete inhibition of trypsin activity does not prevent, or even reduce the conversion of trypsinogen to trypsin [55]. A cell permeant cathepsin B inhibitor, on the other hand, prevented trypsinogen activation completely.…”
Section: Role Of Trypsin In Premature Digestive Protease Activationmentioning
confidence: 99%